The MRL/lpr Mouse Strain as a Model for Neuropsychiatric Systemic Lupus Erythematosus. (10th February 2011) - Gulinello, Maria; Putterman, Chaim
Abstract : To date, CNS disease and neuropsychiatric symptoms of systemic lupus erythematosus (NP-SLE) have been understudied compared to end-organ failure and peripheral pathology. In this review, we focus on a specific mouse model of lupus and the ways in which this model reflects some of the most common manifestations and potential mechanisms of human NP-SLE. The mouse MRL lymphoproliferation strain (a.k.a. MRL/lpr) spontaneously develops the hallmark serological markers and peripheral pathologies typifying lupus in addition to displaying the cognitive and affective dysfunction characteristic of NP-SLE, which may be among the earliest symptoms of lupus. We suggest that although NP-SLE may share common mechanisms with peripheral organ pathology in lupus, especially in the latter stages of the disease, the immunologically privileged nature of the CNS indicates that early manifestations of particularly mood disorders maybe derived from some unique mechanisms. These include altered cytokine profiles that can activate astrocytes, microglia, and alter neuronal function before dysregulation of the blood-brain barrier and development of clinical autoantibody titres.